2012
DOI: 10.1002/nau.22217
|View full text |Cite
|
Sign up to set email alerts
|

Will we ever use stem cells for the treatment of SUI?: ICI‐RS 2011

Abstract: Aims To review the current state of research in the use of stem cells for stress urinary incontinence (SUI) and assess the likelihood of this becoming a relevant treatment option. Methods The peer-reviewed literature consisting of relevant clinical and animal studies on the topic of SUI was surveyed and reviewed. Results Animal studies have demonstrated the potential utility of stem cells in promoting functional recovery of the urethra after simulated childbirth injury. Research in animals suggests similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…[95][96][97] Mesenchymal Stem Cells (MSCs), Muscle-Derived Stem Cells (MDSCs), Adipose-Derived Stem Cells (ADSCs) and Urine-Derived Stem Cells (USCs) are the sources of stem cells investigated for therapeutic benefit in urologic applications. 95,[97][98][99] Clinical trials reported improvement in SUI, through great reduction in pad weight, diaryreported leaks and even a complete achievement of continence in women, with no serious adverse events (pain, bruising at biopsy or injection sites). 95 To date, stem cells have shown promising results for the treatment of voiding dysfunction.…”
Section: Research In Incontinencementioning
confidence: 99%
“…[95][96][97] Mesenchymal Stem Cells (MSCs), Muscle-Derived Stem Cells (MDSCs), Adipose-Derived Stem Cells (ADSCs) and Urine-Derived Stem Cells (USCs) are the sources of stem cells investigated for therapeutic benefit in urologic applications. 95,[97][98][99] Clinical trials reported improvement in SUI, through great reduction in pad weight, diaryreported leaks and even a complete achievement of continence in women, with no serious adverse events (pain, bruising at biopsy or injection sites). 95 To date, stem cells have shown promising results for the treatment of voiding dysfunction.…”
Section: Research In Incontinencementioning
confidence: 99%
“…Multiple animal models using rats and larger animals, such as pig and rabbit, have been employed in these studies as summarized in previous reviews [21][22][23][24][25][26][27][28][29][30][31]. In general, these preclinical studies have provided a proof of concept for using adult stem cells in the treatment of this disorder.…”
Section: Preclinical Studies With Animal Modelsmentioning
confidence: 99%
“…These cell populations include myoblasts, satellite cells, muscle progenitor cells, musclederived cells, and MDSCs [21][22][23][24][25][26][27][28][29][30][31]. These cell populations include myoblasts, satellite cells, muscle progenitor cells, musclederived cells, and MDSCs [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Muscle-derived Stem Cellsmentioning
confidence: 99%
“…Bone marrow-derived mesenchymal cells (BMSCs) are among the best characterized of all stem cells studied so far, with great differentiation ability and being able to secrete factors beneficial for tissue repair [7]. In an animal SUI model, periurethrally injected BMSCs were shown to restore damage to the external urethral sphincter and relieve SUI symptoms [8, 9]. Basic fibroblast growth factor (bFGF) is an FGF family member, and is a growth factor important for the proliferation of mesenchymal stem cells [10, 11], as well as essential to promote the differentiation of the mesenchymal stem cells to fibroblasts [10].…”
Section: Introductionmentioning
confidence: 99%